Effect of Heat Treatment Temperature on Tensile Strenght through Welding of Mild Carbon Steel - Nari, Henny P (INTEK: Jurnal Penelitian, 2022)
This study aims to explain how much the tensile strength of mild steel welding without heat treatment and with heat treatment and to explain how much influence the variation of heat treatment temperature of mild steel welding results on the tensile strength. The method used is the experimental method, namely by conducting experiments in the laboratory, taking data directly on the object to be observed then recording the required data in the form of the initial length of the specimen, the length of the specimen after breaking, the diameter of the initial specimen, the diameter of the specimen after breaking and maximum load. The results showed that the tensile strength value of the mild steel welding without heat treatment was 27.07 kgf/mm2, the tensile strength of the specimen welded by heat treatment at a temperature of 5000C was 29.08 kgf/mm2, at a temperature of 6000C was 35.17 kgf/mm2 and at 7000C the tensile strength is 40.06 kgf/mm2.